Determination of Cell Stiffness Using Polymer Microbeads as Reference - Omeroglu, Sevde; Varol, Rahmetullah; Karavelioglu, Zeynep; Karadag, Aslihan; Basbinar, Yasemin; Oruc, Muhammed Enes; Uvet, Huseyin (IEEE, 2020)
Knowing the mechanical properties of cells is very important in cell detection, analysis of cell activities, diagnosis and drug treatment. The determination of cell stiffness, which used effectively in cell analysis, is carried out with different measurement techniques. In this study, the stiffness of cells is determined by comparison to the displacement of polystyrene microparticles induced by vibration generated by piezoelectric transducers. The difference of stiffness of the cells and polystyrene microparticles is measured using a digital holographic imaging technique.
Keywords: cell stiffness; digital holography; reactive oxygen species; 3D image processing; DIGITAL HOLOGRAPHIC MICROSCOPY; REFRACTIVE-INDEX; LIVING CELLS; Computer Science; Engineering